Urgensi Pengaturan Terhadap Pengangkatan Anak Oleh Orang Tua Tunggal (Single Parent Adoption): Studi Kasus Penetapan NO. 1/PDT.P/2010/PN.KGN Dan Penetapan NO. 180/PDT.P/2012/PN.DPK - Dessy Marliani Listianingsih; Surini Mangundihardjo; Farida Prihatini (Departemen Hukum Perdata, 2020)
This study aims to ﬁnd out the basis of the need to regulate Single Parent Adoption in a legal uniﬁcation in the form of laws that are viewed from the perspective of child welfare and how the legal consequences for adopted children both in terms of family law and the child's relationship with inheritance adoptive parents. This research was carried out in a juridical-normative approach against two determinations of the application for adoption carried out by single parents from two different district courts, the ﬁrst one is from the Kandangan District Court in South Kalimantan and the other one is from Depok District Court. The regulation regarding Single Parent Adoption is considered as an urgent or urgent need that should be regulated by the government and legislators as law makers in Indonesia. The existing regulations or regulations only accommodate the general adoption events, and so are only stipulated in government regulations and social ministerial regulations. Because of the different socio-legal and psychological aspects between adoption carried out in general and those carried out by single parents, regulations that speciﬁ cally regulate adoption by single parents need to be made so that aspects of child protection and well-being remain well protected in the future.